Effect of calcination conditions on phase formation and particle size of Zn3Nb2O8powders synthesized by solid-state reaction - A. Prasatkhetragarn (2018)
The solid-state mixed oxide method via a rapid vibro-milling technique is explored in the preparation of single-phase Zn3Nb2O8powders. The formation of the Zn3Nb2O8phase in the calcined powders has been investigated as a function of calcination conditions by TG-DTA and XRD techniques. Morphology, particle size and chemical composition have been determined via a combination of SEM and EDX techniques. It has been found that the minor phases of unreacted ZnO and Nb2O5precursors and the columbite ZnNb2O6phase tend to form together with the Zn3Nb2O8phase, depending on calcination conditions. It is seen that optimization of calcination conditions can lead to a single-phase Zn3Nb2O8in a monoclinic phase. © 2007 Elsevier B.V. All rights reserved.